Pengetahuan dan Sikap berhubungan dengan Perilaku Penurunan Tekanan Darah pada Lanjut Usia dengan Hipertensi - Hasanah, Nurul; Fatmawati, Tina Yuli; Armina, Armina; Zein, Zafrullah (3031-8572, 2023)
Hypertension is a condition where there is an increase in systolic blood pressure 140 mm Hg or diastolic blood pressure 90 mm Hg. Hypertension is often referred to as the